An update on the role of adipokines in arterial stiffness and hypertension. Issue 3 (March 2015) - Sabbatini, Andréa R.; Fontana, Vanessa; Laurent, Stephane; Moreno, Heitor
<x xml:space="preserve">Abstract</x> Adipokines are hormones produced by adipocytes and have been involved in multiple pathologic pathways, including inflammatory and cardiovascular complications in essential hypertension. Arterial stiffness is a frequent vascular complication that represents increased cardiovascular risk in hypertensive patients. Adipokines, such as adiponectin, leptin and resistin, might be implicated in hypertension, as well as in vascular alterations associated with this condition. Arterial stiffness has proven to be a predictor of cardiovascular events. Obesity and target-organ damage such as arterial stiffness are features associated with hypertension. This review aims to update the association between adipokines and arterial stiffness in essential and resistant hypertension (RHTN).